Comparison of Motor Abilities of Young Children in Poland in the Years 1996 and 2006 - Alicja Drohomirecka; Jerzy Eider; Katarzyna Kotarska; Katarzyna Sygit; Marian Sygit (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
The first study was conducted in 1996 in 10 (i.e. all) nurseries and 11 randomly selected preschools in Szczecin. The study involved 526 children (257 boys and 269 girls) aged 1-4 years, and 865 children from preschools (448 boys and 417 girls) aged 4-7 years. In 2006, the study was repeated in seven nurseries (i.e. all nurseries that existed in Szczecin at the time) and 11 preschools in the city of Szczecin, i.e. the same as in 1996. The study involved 314 children attending nurseries: 169 boys and 145 girls aged 1.5-4 and 887 preschool children (461 boys and 426 girls) aged 4-6 years. Motor development of nursery children was assessed based on the Denver test in two selected areas. The level of motor development in preschool children was assessed on the basis of a modified Wrocław Physical Fitness Test developed by B. Sekita. Comparison of the results helped answer the question whether and what developmental changes took place over a decade. The results indicated that the level of motor development of children in Szczecin, compared with children examined 10 years earlier, showed no significant differences.